2017
DOI: 10.1093/mnras/stx1515
|View full text |Cite
|
Sign up to set email alerts
|

MUSE deep-fields: the Ly α luminosity function in the Hubble Deep Field-South at 2.91 < z < 6.64

Abstract: We present the first estimate of the Lyα luminosity function using blind spectroscopy from the Multi Unit Spectroscopic Explorer, MUSE, in the Hubble Deep Field South. Using automatic source-detection software, we assemble a homogeneously-detected sample of 59 Lyα emitters covering a flux range of −18.0 < log 10 (F) < −16.3 (erg s −1 cm −2 ), corresponding to luminosities of 41.4 < log 10 (L) < 42.8 (erg s −1 ). As recent studies have shown, Lyα fluxes can be underestimated by a factor of two or more via tradi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…With this data we were able to improve the number of known spectroscopic redshifts in this tiny region by an order of magnitude (Bacon et al 2015). This first experiment not only effectively demonstrated the unique capabilities of MUSE in this context, but has also led to new scientific results: the discovery of extended Lyα halos in the circumgalactic medium around high redshift galaxies (Wisotzki et al 2016), the study of gas kinematics (Contini et al 2016), the investigation of the faint-end of the Lyα luminosity function (Drake et al 2017a), the measurement of metallicity gradients (Carton et al 2017) and the properties of galactic winds at high z (Finley et al 2017a).…”
Section: Introductionmentioning
confidence: 71%
“…With this data we were able to improve the number of known spectroscopic redshifts in this tiny region by an order of magnitude (Bacon et al 2015). This first experiment not only effectively demonstrated the unique capabilities of MUSE in this context, but has also led to new scientific results: the discovery of extended Lyα halos in the circumgalactic medium around high redshift galaxies (Wisotzki et al 2016), the study of gas kinematics (Contini et al 2016), the investigation of the faint-end of the Lyα luminosity function (Drake et al 2017a), the measurement of metallicity gradients (Carton et al 2017) and the properties of galactic winds at high z (Finley et al 2017a).…”
Section: Introductionmentioning
confidence: 71%
“…This allows us to draw more solid conclusions than those from our 1 × 1 pilot study of the HDFS field (Drake et al 2017).…”
Section: Luminosity Functionsmentioning
confidence: 87%
“…In Drake et al (2017) we discussed the difference in the apparent luminosity function when using different approaches to estimate total Lyα flux. We concluded that using a curve-of-growth analysis provided the most accurate measure of F Lyα although noted that this approach introduced the possibility of a bias in the fraction of the flux recovered according to true total flux.…”
Section: Flux Recovery Of Simulated Emittersmentioning
confidence: 99%
See 2 more Smart Citations